Implementation of the Deep Learning Approach in Aqidah Akhlak Instruction to Develop Critical Thinking - Irfan Prasetia; Gusli Bambang Irawan (IQRO: Journal of Islamic Education, 2026)
Learning in Aqidah Akhlak requires instructional approaches that foster meaningful understanding, reflective thinking, and active student engagement rather than rote memorization. This study aims to analyze the implementation of the Deep Learning approach in Aqidah Akhlak instruction and examine its contribution to developing students' critical thinking skills at MAN 3 Palembang. A qualitative case study design was employed. Data were collected through classroom observations, semi-structured interviews, and document analysis, and analyzed using the interactive model of data reduction, data display, and conclusion drawing. The trustworthiness of the findings was ensured through source and technique triangulation. The findings indicate that the integration of meaningful learning, mindful learning, and joyful learning encourages students to actively construct knowledge, reflect on Islamic values, and develop logical reasoning in addressing contextual problems. The implementation of the Deep Learning approach is supported by teacher competence, institutional commitment, and a conducive learning environment, although differences in students' readiness and limited learning resources remain challenges. These findings provide empirical evidence that the Deep Learning approach offers an effective pedagogical framework for strengthening critical thinking while fostering meaningful religious learning in Islamic secondary education.